The effect of the parameters of a vibration-based impact mode piezoelectric power generator - Basari, Amat Amir; Sosuke, Awaji; Seiji, Hashimoto; Shintaro, Sakamoto; Bunji, Homma; Kenji, Suto; Hiroaki, Okada; Hideki, Okuno; Kojiro, Kobayashi; Shunji , Kumagai (Hindawi Publishing Corporation, 2015)
This study reports the effects of the parameters of a vibration-based impactmode piezoelectric power generator. First, an evaluation of the effects of the impact parameters, the mass, and the impact velocity is presented. It is found that the output voltage of the piezoelectric device in impactmode is directly proportional to the velocity,whereas the output power is equal to a quadratic function of the same variable. For the same impact momentum, the effect of the velocity in generating a higher peak output is dominant compared with the mass. Second, the vibration-based impact mode piezoelectric power generator is discussed. The experimental results show that a wider operating frequency bandwidth of the output power can be achieved with the preloading configuration. However, regardingmagnitude, due to the high velocity of impact, the configurationwith a gap between the tip and the piezoelectric device produces a higher output.